The Recent Evolution of Wisconsin Public Worker Unionism since Act 10. (June 2020) - Nack, David; Childers, Michael; Kulwiec, Alexia; Ibarra, Armando
This paper examines the experience of four major public sector unions in Wisconsin since the passage of Wisconsin Act 10 in 2011. The four unions are the American Federation of State, County and Municipal Employees (AFSCME), the American Federation of Teachers (AFT-Wisconsin), the Service Employees International Union (SEIU), and the Wisconsin Education Association Council (WEAC), an affiliate of the National Education Association. Wisconsin's prior legal framework for public sector collective bargaining is explained and compared to the new highly restrictive framework established by Act 10. That new framework, established by state legislation, is analyzed, as are its impacts on the membership, revenues, structures, and practices of the four unions. In general, we find the impacts to have been very dramatic, with a loss of active union membership averaging approximately 70 percent overall, and concomitant dramatic losses in union revenues and power. These shocks have engendered the restructuring of two of the unions examined, the downsizing of the third, and the de facto exiting from the state's public sector in another. There have also been significant changes in representation practices in one union, but less so in the others. We conclude by discussing best union practices based on this experience, as well as considering what the recent public sector union history in Wisconsin may portend for public worker union membership nationwide, since the issuing of the Janus Decision by the U.S. Supreme Court.